Pengaruh Kepanduaan Hizbul Wathan (HW) terhadap Pendidikan Karakter Anak Usia 5–6 Tahun di TK ‘Aisyiyah Bustanul Atfhal I Kota Probolinggo - Millah, Kamalatul; Dheasari, Agustiarini Eka (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Character education from an early age is an important foundation in shaping children's attitudes and Character education from an early age is an important foundation in shaping children's attitudes and behaviors, which will affect their future development. Through extracurricular activities, children can hone their potential, talents and interests while building an independent and happy attitude that has a positive impact on themselves, their families and society. One extracurricular activity that is effective in character education is Hizbul Wathan Scouting. The purpose of this study was to investigate how Hizbul Wathan Scouting activities affect the character development of five- to six-year-old children attending 'Aisyiyah Bustanul Athfal I Kindergarten in Probolinggo City. Thirty children were divided into two groups for this study, namely the experimental group and the control group, using an experimental approach using a pre-test post-test design on the control group. For eight weeks, from September to October 2024, the experimental group participated in Hizbul Wathan activities. The character assessment used a rubric that included aspects of independence, discipline, honesty, cooperation, and respect. A significant value (2-tailed) of 0.00 < 0.05 was found in the results of data analysis using the t-test and Kolmogorov-Smirnov test, indicating that Hizbul Wathan activities have a beneficial impact on early childhood character education.